Atypical Brain Mechanisms of Prediction According to Uncertainty in Autism - Thillay, Alix; Lemaire, Mathieu; Roux, Sylvie; Houy-Durand, Emmanuelle; Barthélémy, Catherine; Knight, Robert T.; Bidet-Caulet, Aurélie; Bonnet-Brilhault, Frédérique (Frontiers in Neuroscience, 2016)
Resistance to change is often reported in autism and may arise from an inability to predict events in uncertain contexts. Using EEG recorded in 12 adults with autism and age-matched controls performing a visual target detection task, we characterized the influence of a certain context (targets preceded by a predictive sequence of three distinct stimuli) or an uncertain context (random targets) on behavior and electrophysiological markers of predictive processing. During an uncertain context, adults with autism were faster than controls to detect targets. They also had an enhancement in CNV amplitude preceding all random stimuli – indexing enhanced preparatory mechanisms, and an earlier N2 to targets – reflecting faster information processing – compared to controls. During a certain context, both controls and adults with autism presented an increase in P3 amplitude to predictive stimuli – indexing information encoding of the predictive sequence, an enhancement in CNV amplitude preceding predictable targets – corresponding to the deployment of preparatory mechanisms, and an earlier P3 to predictable targets – reflecting efficient prediction building and implementation. These results suggest an efficient extraction of predictive information to generate predictions in both controls and adults with autism during a certain context. However, adults with autism displayed a failure to decrease mu power during motor preparation accompanied by a reduced benefit in reaction times to predictable targets. The data reveal that patients with autism over-anticipate stimuli occurring in an uncertain context, in accord with their sense of being overwhelmed by incoming information. These results suggest that adults with autism cannot flexibly modulate cortical activity according to changing levels of uncertainty.